2022
DOI: 10.3390/molecules27103152
|View full text |Cite
|
Sign up to set email alerts
|

Targeted and Untargeted Mass Spectrometry-Based Metabolomics for Chemical Profiling of Three Coffee Species

Abstract: While coffee beans have been studied for many years, researchers are showing a growing interest in coffee leaves and by-products, but little information is currently available on coffee species other than Coffea arabica and Coffea canephora. The aim of this work was to perform a targeted and untargeted metabolomics study on Coffea arabica, Coffea canephora and Coffea anthonyi. The application of the recent high-resolution mass spectrometry-based metabolomics tools allowed us to gain a clear overview of the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…could differentiate the species metabolic profiles of leaf and fruit extracts. Additionally, five phytochemicals (caffeine, mangiferin and three caffeoylquinic acids) were identified, corroborating the identity of the differentiated metabolites between species and tissues (Montis et al, 2022). Also, Zhang et al characterized cyclopeptides in 20 species of Rubia sp.…”
Section: A B Cmentioning
confidence: 62%
See 2 more Smart Citations
“…could differentiate the species metabolic profiles of leaf and fruit extracts. Additionally, five phytochemicals (caffeine, mangiferin and three caffeoylquinic acids) were identified, corroborating the identity of the differentiated metabolites between species and tissues (Montis et al, 2022). Also, Zhang et al characterized cyclopeptides in 20 species of Rubia sp.…”
Section: A B Cmentioning
confidence: 62%
“…However, it has been mostly applied to crops such as rice, wheat, barley and potatoes (McSorley and Phillips, 1992;Peleg et al, 2005;Feuillet et al, 2008;Spooner et al, 2014;Brar and Khush, 2018). Despite the limited number of studies on coffee leaf and other Rubiaceae metabolic content, the presence of phenolic compounds has been previously described (Souard et al, 2018;Cangeloni et al, 2022;Montis et al, 2022). Caffeine, chlorogenic acids, mangiferin and trigonelline are the main phytochemicals found in coffee leaves (Cangeloni et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may allow, also in the absence of analytical standards, us to annotate plant metabolites by taking advantage of the large online repositories and database available for plant metabolomics, such as PlantCyc . The application of HR-MS-based techniques has recently allowed a more thorough description of the wide variety of secondary metabolites occurring in coffee leaves, along with the simultaneous detection of entire molecular families. However, few papers have investigated the potential effect of such techniques on the postharvest processing of coffee leaves and the phytochemical modifications involved . This approach allows the untargeted comparison of large analytical data in several herbal plants and spices, leading to not only the discrimination of plants with distinct geographical origin but also the classification of different styles of postharvest management. …”
Section: Introductionmentioning
confidence: 99%
“…Other than alkaloids, phenolic acids present in coffee have potential antioxidant, hepatoprotective, hypoglycemic, and antiviral activities [10]. However, most of the metabolome analysis studies have reported the composition of green coffee (C. arabica) or C. anthonyi and C. canephora [11]. Since the berries are the commercial starting point for coffee production, it is important to understand how berries of different colors differ in chemistry.…”
Section: Introductionmentioning
confidence: 99%